The impact of CD3ζ ITAM multiplicity and sequence on CAR T-cell survival and function - Majumdar, Shubhabrata; Echelibe, Hilda; Bettini, Maria; Bettini, Matthew L. (Frontiers in Immunology, 2025)
IntroductionChimeric antigen receptor (CAR) expressing T-cells have shown great promise for the future of cancer immunotherapy with the recent clinical successes achieved in treating different hematologic cancers. Despite these early successes, several challenges remain in the field that require to be solved for the therapy to be more efficacious. One such challenge is the lack of long-term persistence of CD28 based CAR T-cells in patients. Although, CD28 based CAR T-cells elicit a robust acute anti-tumor response, they are more prone to early exhaustion, terminal differentiation and cell death due to their strong signaling patterns. Hence attenuation of signaling strength in CD28 based CARs is an accepted strategy to improve long-term CAR T-cell function and persistence in patients. Previous studies with the conventional T-cell receptor (TCR) have suggested that manipulation of CD3 immunoreceptor tyrosine-based activation motif (ITAM) sequences can alter TCR signaling strength. Based on these studies, we have designed 2nd generation murine anti-CD19 CD28 based CARs with restricted CD3ζ ITAM sequence diversity while maintaining a multiplicity of three. They are called ζAAA, ζBBB and ζCCC based on which CD3ζ ITAM they express. The goal of the study is to understand the non-redundant signaling properties of the individual CD3ζ ITAMs and their effect on CAR T-cell function. We hypothesized that the individual CD3ζ ITAMs will exhibit unique signaling properties in the ITAM restricted CARs which may allow for optimization of CAR signaling and improve CAR T-cell persistence and function.MethodWe subjected the ITAM restricted CAR T cells to various conditions of in vitro stimulation using CD19+ tumor cells or CD19-coated magnetic beads. Immunoblotting and flow cytometry based Ca2+ signaling assays were used to quantify signaling differences. Functional differences were studied using in vitro cytotoxicity, degranulation and cytokine expression assays. CAR T cell exhaustion and differentiation were studied using an in vitro exhaustion assay.ResultsWe observed that ζAAA CARs had stronger signaling strength compared to ζBBB and ζCCC CARs. The signaling differences were reflected in their functional activation profiles with T-cells expressing ζAAA CARs having a strong activation profile and ζCCC CARs having a weak activation profile. ζCCC CAR T cells were less prone to differentiation and exhaustion.DiscussionSince, weaker signaling ζCCC CARs favored less cell death, exhaustion and differentiation, they might be better candidates for improving long term survival and persistence of CAR T cells in patients.